Biometrical study of internal genital organs of Gaddi goats - SHALINI,; SHARMA, D N (The Indian Journal of Animal Reproduction, 2023)
Female genitalia from 51 healthy non-pregnant Gaddi goats were used for study. Almond shaped ovaries measuredl.57x l.l lx0.83cm in length, width and thickness respectively. Isthmus part of oviduct form "S" or "U" shaped curve beforeterminting into uterine horn. The corpus uteri was longer (1.60cm) than cervix uteri (1.20cm).
Keywords: Biometry; internal genital organs; Gaddi goat